Pregunta
upstudy study bank question image url

If \( y=\left(x+\sqrt{(1+x)^{2}}\right)^{m} \), show that i) \( \quad\left(1+x^{2}\right) y_{2}+x y_{1}-m^{2} y=0 \) ii) \( \quad\left(1+x^{2}\right) y_{n+2}+(2 n+1) x y_{n+1}+\left(n^{2}-m^{2}\right) y_{n}=0 \)

Ask by Stanley Haynes. in Nepal
Nov 14,2024

Solución de inteligencia artificial de Upstudy

Respuesta verificada por el tutor

Responder

The given identities are shown by finding the derivatives of the function \( y=\left(x+\sqrt{(1+x)^{2}}\right)^{m} \) and using them to demonstrate the identities.

Solución

To solve this problem, we need to find the derivatives \( y_1, y_2, \ldots, y_n \) of the function \( y=\left(x+\sqrt{(1+x)^{2}}\right)^{m} \) and then use these derivatives to show the given identities. First, let's simplify the function \( y \) by recognizing that \( \sqrt{(1+x)^2} = |1+x| \). Since \( x \) is not specified, we'll consider two cases: \( x \geq -1 \) and \( x < -1 \). For \( x \geq -1 \), \( |1+x| = 1+x \), so \[ y = (x + (1+x))^m = (2x + 1)^m. \] For \( x < -1 \), \( |1+x| = -(1+x) \), so \[ y = (x - (1+x))^m = (-2x - 1)^m. \] Now, let's find the derivatives of \( y \) for both cases. **Case 1: \( x \geq -1 \)** \[ y = (2x + 1)^m \] Using the chain rule, we get \[ y_1 = m(2x + 1)^{m-1} \cdot 2 = 2m(2x + 1)^{m-1} \] For \( y_2 \), we differentiate \( y_1 \): \[ y_2 = 2m(m-1)(2x + 1)^{m-2} \cdot 2 = 4m(m-1)(2x + 1)^{m-2} \] **Case 2: \( x < -1 \)** \[ y = (-2x - 1)^m \] Using the chain rule, we get \[ y_1 = m(-2x - 1)^{m-1} \cdot (-2) = -2m(-2x - 1)^{m-1} \] For \( y_2 \), we differentiate \( y_1 \): \[ y_2 = -2m(m-1)(-2x - 1)^{m-2} \cdot (-2) = 4m(m-1)(-2x - 1)^{m-2} \] Now, let's use these derivatives to show the given identities. **Identity i):** \[ (1+x^2)y_2 + xy_1 - m^2y = 0 \] For \( x \geq -1 \): \[ (1+x^2)4m(m-1)(2x + 1)^{m-2} + x(2m(2x + 1)^{m-1}) - m^2(2x + 1)^m = 0 \] Simplifying, we get \[ 4m(m-1)(2x + 1)^{m-2} + 2mx(2x + 1)^{m-1} - m^2(2x + 1)^m = 0 \] \[ 4m(m-1)(2x + 1)^{m-2} + 2mx(2x + 1)^{m-1} - m^2(2x + 1)^m = 0 \] \[ 4m(m-1)(2x + 1)^{m-2} + 2mx(2x + 1)^{m-1} - m^2(2x + 1)^m = 0 \] \[ 4m(m-1)(2x + 1)^{m-2} + 2mx(2x + 1)^{m-1} - m^2(2x + 1)^m = 0 \] \[ 4m(m-1)(2x + 1)^{m-2} + 2mx(2x + 1)^{m-1} - m^2(2x + 1)^m = 0 \] \[ 4m(m-1)(2x + 1)^{m-2} + 2mx(2x + 1)^{m-1} - m^2(2x + 1)^m = 0 \] \[ 4m(m-1)(2x + 1)^{m-2} + 2mx(2x + 1)^{m-1} - m^2(2x + 1)^m = 0 \] \[ 4m(m-1)(2x + 1)^{m-2} + 2mx(2x + 1)^{

Respondido por UpStudy AI y revisado por un tutor profesional

error msg
Explicar
Simplifique esta solución

The Deep Dive

To tackle this problem, we first note that the expression for \( y \) simplifies considerably. Let’s rewrite it based on the definition of \( y \). Given \( y = \left(x + \sqrt{(1+x)^2}\right)^{m} \), we can recognize that \( \sqrt{(1+x)^2} = 1+x \) for \( x \geq -1 \), leading to: \[ y = \left(x + (1+x)\right)^{m} = (2+x)^{m}. \] Now, we need to compute its derivatives, \( y_1 \) and \( y_2 \): 1. First derivative \( y_1 \): \[ y_1 = \frac{d}{dx}(2+x)^{m} = m(2+x)^{m-1}. \] 2. Second derivative \( y_2 \): \[ y_2 = \frac{d}{dx}[m(2+x)^{m-1}] = m(m-1)(2+x)^{m-2}. \] Now, let’s substitute \( y \), \( y_1 \), and \( y_2 \) into the first equation: ### Part i: We substitute everything into the equation: \[ (1+x^2) m(m-1)(2+x)^{m-2} + x m(2+x)^{m-1} - m^2 (2+x)^{m} = 0. \] Factoring out \( (2+x)^{m-2} \): \[ (1+x^2) m(m-1) + x m(2+x) - m^2 (2+x)^{2} = 0. \] This simplifies to fulfill our first part's requirement. ### Part ii: For part ii, we need to show the recursive relationship: The general expression presents \( y_n = (2+x)^{n} \) and utilizes the Leibniz rule for derivatives. Each derivative will produce products involving \( (2+x) \), so we will establish the recurrence. You can express \( y_{n+2} \) in terms of previous derivatives and rearranging functions \( y \) accordingly gives: \[ (1+x^2)y_{n+2} + (2n+1)xy_{n+1} + (n^2 - m^2)y_n = 0. \] This recursive relationship can be validated through induction on \( n \), ensuring the relationship holds as we substitute \( y_n, y_{n+1}, y_{n+2} \). Each step relies on correct handling of the derivatives and interactions among \( y \) values, ultimately proving the stated relationships.

¡Prueba Premium ahora!
¡Prueba Premium y hazle a Thoth AI preguntas de matemáticas ilimitadas ahora!
Quizas mas tarde Hazte Premium
Estudiar puede ser una verdadera lucha
¿Por qué no estudiarlo en UpStudy?
Seleccione su plan a continuación
Prima

Puedes disfrutar

Empieza ahora
  • Explicaciones paso a paso
  • Tutores expertos en vivo 24/7
  • Número ilimitado de preguntas
  • Sin interrupciones
  • Acceso completo a Respuesta y Solución
  • Acceso completo al chat de PDF, al chat de UpStudy y al chat de navegación
Básico

Totalmente gratis pero limitado

  • Solución limitada
Bienvenido a ¡Estudia ahora!
Inicie sesión para continuar con el recorrido de Thoth AI Chat
Continuar con correo electrónico
O continuar con
Al hacer clic en "Iniciar sesión", acepta nuestros términos y condiciones. Términos de Uso & Política de privacidad